2022
DOI: 10.1111/ijfs.15630
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative characteristics and gel properties of porcine myofibrillar proteins affected by l‐lysine and l‐histidine in a dose‐dependent manner at a low and high salt concentration

Abstract: Summary This study investigated the effects of l‐lysine (Lys) and l‐histidine (His) on the oxidative characteristics and gel properties of porcine myofibrillar proteins (MP). Results showed that Lys and His had a strong ferrous ion‐chelating ability and hydroxyl radical‐scavenging activity. Moreover, Lys and His inhibited the protein carbonyl formation and MP aggregation at 0.2 M and 0.6 M NaCl, respectively, in a dose‐dependent manner. Furthermore, 2 and 4 mg mL−1 Lys and His decreased the oxidation‐induced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…In contrast, the oxidized MPs gel at 0.6 M NaCl showed a loose lamellar structure with more and larger pores, suggesting that oxidation induced the destruction of gel structure. This is consistent with the research of Guo et al [ 17 ], which showed that the gel structure of an oxidized MPs gel at 0.6 M NaCl was rough and cracked.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, the oxidized MPs gel at 0.6 M NaCl showed a loose lamellar structure with more and larger pores, suggesting that oxidation induced the destruction of gel structure. This is consistent with the research of Guo et al [ 17 ], which showed that the gel structure of an oxidized MPs gel at 0.6 M NaCl was rough and cracked.…”
Section: Resultssupporting
confidence: 93%
“…The surface hydrophobicity of MPs may reflect the extent of unfolding of MPs and is a considerable molecular characteristic associated with MPs functionality [ 17 ]. The effects of HYP on the surface hydrophobicity of the samples were examined ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations